2020
DOI: 10.3389/fphar.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

The Glucagon-Like Peptide-1 Analogue Liraglutide Reduces Seizures Susceptibility, Cognition Dysfunction and Neuronal Apoptosis in a Mouse Model of Dravet Syndrome

Abstract: Moreover, liraglutide protected against Scn1a KO-induced apoptosis, which was manifested in the phosphorylation of mTOR (KO+NS: 1.99 ± 0.31 vs. KO+Lira: 0.97 ± 0.18, P = 0.0004), as well as the downregulation of cleaved caspase-3 (KO+NS: 0.49 ± 0.04 vs. KO+Lira: 0.30 ± 0.01, P = 0.0003) and restoration of the imbalance between BAX (KO+NS: 0.90 ± 0.02 vs. KO +Lira: 0.75 ± 0.04, P = 0.0005) and BCL-2 (KO+NS: 0.46 ± 0.02 vs. KO+Lira: 0.61 ± 0.02, P = 0.0006). Collectively, these results show that liraglutide redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
(75 reference statements)
3
17
0
Order By: Relevance
“…Neuronal damage to GABAergic arborization includes cortical necrosis and disorderly cellular architecture and produces a phenotype related to the underlying Scn1a genetic defect, but seizure-related excitotoxic damage also causes neurodegeneration. Neurodegeneration is evident in Scn1a−/− mice as necrosis in cortical regions at 14 days following onset of epileptic activity [31]. Cortical damage was accompanied by apoptosis, mTOR activation indicating metabolic stress, and poor performance on four cognitive function tests evaluating learning and spatial memory [31].…”
Section: Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuronal damage to GABAergic arborization includes cortical necrosis and disorderly cellular architecture and produces a phenotype related to the underlying Scn1a genetic defect, but seizure-related excitotoxic damage also causes neurodegeneration. Neurodegeneration is evident in Scn1a−/− mice as necrosis in cortical regions at 14 days following onset of epileptic activity [31]. Cortical damage was accompanied by apoptosis, mTOR activation indicating metabolic stress, and poor performance on four cognitive function tests evaluating learning and spatial memory [31].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Neurodegeneration is evident in Scn1a−/− mice as necrosis in cortical regions at 14 days following onset of epileptic activity [31]. Cortical damage was accompanied by apoptosis, mTOR activation indicating metabolic stress, and poor performance on four cognitive function tests evaluating learning and spatial memory [31].…”
Section: Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 receptors are widely expressed in various structures, such as the brainstem, cerebral cortex and hippocampus (23,24). Moreover, an increasing number of studies have suggested that GLP-1 signaling may serve as a potential drug target for the management of various neurological disorders, including epilepsy and its associated comorbidities (20,25). Semaglutide entered the market in 2017 as a novel once-weekly GLP-1 analogue for the treatment of type II diabetes (26).…”
Section: Semaglutide Attenuates Seizure Severity and Ameliorates Cognitive Dysfunction By Blocking The Nlr Family Pyrin Domain Containingmentioning
confidence: 99%
“…Briefly, after the mice were anaesthetized with 60 mg/kg sodium pentobarbital, a stereotactic device was used to implant electrodes into the cerebral cortex on both sides of the bregma. The specific method for implanting the intracranial electrodes was the same as that used in our previous study (25). On the 45th day, seizure severity was assessed, and ECoG was recorded using an information integrated biological signal acquisition and processing system (BL-420 N; Techman).…”
Section: Western Blotting (Wb)mentioning
confidence: 99%